Calculation of the size of a hollow workpiece with a thin wall with interchangeabe thickness and determination of the parameters of its crimping in a matrix with a cone-cylindrical deforming surface - Volodymyr Kaliuzhnyi; Oleksandr Kaliuzhnyi; Kostiantyn Marchuk (Mechanics and Advanced Technologies)
The article is devoted to the production of conical hollow products with a cylindrical part and a thin wall with different thickness in height from low-carbon steel. The finite element method was used to determine the shape and dimensions of the original hollow workpiece, as well as the parameters of cold crimping of such a workpiece. The shape and dimensions of the original workpiece are determined by a two-stage simulation of the alignment of the product wall in height with the achievement of the cylindrical outer surface. At the first stage, the straightening is simulated by expansion with the help of a punch of the cylindrical part of the wall and the place of transition of the cylindrical part to the conical one. At the second stage, the cylindrical outer surface of the wall is reached by punching. Upon receipt of the original workpiece, the wall becomes thinner and its height increases. Such an original crimp blank can be obtained in two passes using extrusion and thinning stretching operations. In the analysis of crimping in a matrix with a conical and cylindrical deforming surface, an elastic-plastic metal model was used. The dependences of the crimping force and the force of pushing the product out of the matrix on the movement of the deforming tool are determined. The stress-strain state of the deformed workpiece at the end of crimping is determined. the final shape and dimensions of the product are determined. The results of crimping simulation, in which the wall thickening occurs, confirmed the possibility of calculating the shape and size of the workpiece. Prediction of the yield stress of the deformed metal along the height of the wall of the product was carried out from the distribution of the intensity of deformations.